Surveillance of drug prescribing: why outliers miss their targets – a qualitative study - Julia Gollnick; Nikoletta Zeschick; Franziska Hörbrand; Peter Killian; Maria Sebastiao; Thomas Kühlein; Norbert Donner-Banzhoff (BMC Health Services Research)
Abstract Background Rising costs are a challenge for healthcare systems. To keep expenditure for drugs under control, in many healthcare systems, drug prescribing is continuously monitored. The Bavarian Drug Agreement (German: Wirkstoffvereinbarung or WSV) for the ambulatory sector in Bavaria (the federal state of Germany) was developed for this purpose. Physicians must reach defined drug target quotas for prescribing generic drugs and certain recommended drugs specified and measured with defined daily doses (DDD). A subgroup of physicians, known as outliers, may miss their drug targets. The objective of this qualitative study was to understand the reasons physicians miss their targets. Methods We identified outliers based on drug prescribing data from the association of statutory health insurance (SHI)-accredited physicians (KV). Outliers were invited to participate in semi-structured interviews. Results Out of 401 outliers thus identified n = 26 physicians were interviewed. Their prescribing behaviours are affected by competing demands regarding drug decisions, such as saving staff time, costs, and discussions with patients. Often, their freedom to prescribe is limited by previous prescribers. Ease of administration of drugs not recommended also plays a role. Uncritical enthusiasm regarding the effectiveness and safety of drugs with recommendations, often reinforced by pharmaceutical marketing, leads to missed targets. Some physicians have coping strategies to avoid becoming outliers. Conclusions Investigating physicians not meeting their targets helps us understand beliefs and barriers for appropriate drug prescribing. Based on these kinds of findings, surveillance procedures can be improved, and physicians can receive support to meet targets in the future. Trial registration This trial has been registered in the German Register of Clinical Trials (DRKS: DRKS00016161; registration date 07. December 2018).